Mental Health and Quality of Life for Health Workers During the COVID-19 Pandemic: A Systematic Review - Kotijah, Siti; Wahyuni, Lutfi (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2022)
Background: COVID-19, a strain of the coronavirus that causes acute respiratory syndrome, first appeared in the Chinese city of Wuhan and quickly spread throughout the world in early 2020. The COVID-19 pandemic has changed health care systems around the world and affected the mental health of healthcare workers and their quality of life.Aim: to review the existing scientific evidence regarding mental health and quality of life of health workers during the COVID-19 pandemic. Methods: This study was taken from the pubmed, ScienceDirect, and Ebsco databases identified between December 2019 to July 2021 and was limited to peer-reviewed research written in English, quantitative research on mental health and quality of life with a cross sectional approach. Articles that fit the criteria are then analyzed using the critical appraisal tool that is appropriate for results of the research. Results: The results showed an increase in mental disorders, including stress, anxiety, depression, and PTSD in health workers. This is caused by several factors, namely 1) stressors that contribute to the work environment 2) work pressure components, 3) epidemic components, 4) family-related components. This condition can affect the quality of life of health workers. Conclusion: Research evaluating the direct and indirect association of mental disorders on the mental health of healthcare professionals is urgently needed to improve treatment, mental health care planning and for preventive measures during a potential next pandemic.